Three-level zero-voltage transition interleaved buck converter with DC transformer-based isolation for EV fast charging stations - Amin, Saghir (2024)
This paper proposes a new design architecture in which a three-level zero-voltage transition interleaved buck converter (3L-ZVT-IBC) with DC transformer-based isolation is introduced for applications in EV fast charging stations. This 3L-ZVT-IBC accomplishes lossless switching thanks to ZVT ability of proposed idea, enabling a high efficiency. In addition, it also has a lower voltage stress in comparison to the conventional interleaved buck converter, still required duty-cycle lies in the vicinity of 50% for wide operating range of output voltage required for EV fast charging stations (200 V to 850 V). In addition, the proposed architecture guarantees that the multilevel input DC voltages are balanced without any specific balancing technique or extra components, while ensuring the operation with low output inductor ripple for all conditions. In order to validate the 3L-ZVT-IBC, PSIM simulations were carried out, demonstrating the feasibility of the proposed 3L-ZVT-IBC.